RANKING OF THE COMMERCIAL ORGANIZATONS MANAGERS’ SALARY: PROBLEMS AND SOLUTIONS - О. І. Яковлєв (Ринкова економіка: сучасна теорія і практика управління)
Managers are a key resource for the commercial organization, determining its competitiveness.  The desire of managers to operate effectively and efficiently depends on how they perceive the company operating the system of payment for their work. If managers understand that the size of salaries, established and differentiated subjectively, this salary does not encourage them to the faithful implementation of their official duties. This research, conducted by the author in small and medium business entities of Ukraine, allows concluding that there is an absence of a systematic, science-based and objective approach to the establishment of the size of managers’ salaries and their differentiation. The analysis, used to rank salary grading techniques, calls into question the scientific validity of the choice of adequate universal factors and criteria for all job positions at the organization to assess the quantification of job positions and salaries. The author proposes to abandon the search for universal factors and criteria for the evaluation of all job positions of the organization. Instead, another solution is suggested, i.e. the grouping them on the basis of the uniformity of work processes, which are performed, and then for each group to identify a set of factors and criteria to quantify the importance of these factors. Comparing the sum of the factors of job positions it can be possible to perform ranking of basic salaries. The managers’ official positions of the commercial organization to merge into a single group on the grounds that all managerial positions are assumed to exercise the functions of management with the control objects that is the various business processes. As a result it is possible to evaluate the complexity of the control functions and measured values can appreciate the complexity of managers’ job positions of any commercial organizations and to carry out the ranking of salaries if to identify the characteristics of business processes affecting.